How does biochar influence soil N cycle? A meta-analysis - Liu, Qi; Zhang, Yanhui; Liu, Benjuan; Amonette, James E.; Lin, Zhibin; Liu, Gang; Ambus, Per; Xie, Zubin (Plant and soil, 2018)
Background and aims Modern agriculture is driving the release of excessive amounts of reactive nitrogen (N) from the soils to the environment, thereby threatening ecological balances and functions. The amendment of soils with biochar has been suggested as a promising solution to regulate the soil N cycle and reduce N effluxes. However, a comprehensive and quantitative understanding of biochar impacts on soil N cycle remains elusive. Methods A meta-analysis was conducted to assess the influence of biochar on different variables involved in soil N cycle using data compiled across 208 peer-reviewed studies. Results On average, biochar beneficially increases symbiotic biological N 2 fixation (63%), improves plant N uptake (11%), reduces soil N 2 O emissions (32%), and decreases soil N leaching (26%), but it poses a risk of increased soil NH 3 volatilization (19%). Biochar-induced increase in soil NH 3 volatilization commonly occurs in studies with soils of low buffering capacity (soil pH ≤ 5, organic carbon≤10 g kg −1 , or clay texture), the application of high alkaline biochar (straw- or manure-derived biochar), or biochar at high application rate (>40 t ha −1 ). Besides, if the pyrolytic syngas is not purified, the biochar production process may be a potential source of N 2 O and NO x emissions which correspond to 2–4% and 3–24% of the feedstock-N, respectively. Conclusions This study suggests that to make biochar beneficial for decreasing soil N effluxes, clean advanced pyrolysis technique and adapted use of biochar are of great importance.